2013
DOI: 10.1016/j.cor.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Achieving MILP feasibility quickly using general disjunctions

Abstract: Branch and bound algorithms for Mixed-Integer Linear Programming (MILP) almost universally branch on a single variable to create disjunctions. General linear expressions involving multiple variables are another option for branching disjunctions, but are not used for two main reasons: (i) descendent LPs tend to solve more slowly because of the added constraints, so the overall solution time is increased, and (ii) it is difficult to quickly find an effective general disjunction. We study the use of general disju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Recent work by Mahmoud and Chinneck (2013) showed that general branching disjunctions can help reach feasible solutions quickly without sacrificing computational efficiency. This is achieved by heuristically constructing general disjunctions fast, and including them only if they are likely to help.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Mahmoud and Chinneck (2013) showed that general branching disjunctions can help reach feasible solutions quickly without sacrificing computational efficiency. This is achieved by heuristically constructing general disjunctions fast, and including them only if they are likely to help.…”
Section: Introductionmentioning
confidence: 99%
“…Branching on general disjunctions lies at the core of Lenstra's algorithm for integer programming in fixed dimension [20]. It has also been used, for example, for special ordered sets [3], exploiting flatness [9], achieving feasibility [21], and symmetry handling [22].…”
Section: Introductionmentioning
confidence: 99%
“…, e n }, in which case we say the algorithm uses variable disjunctions. However, many results explore the benefit of additional directions: various subsets of {−1, 0, 1} n are explored in [24,26,29]; directions derived from mixed integer Gomory cuts are explored in [8,18]; directions derived using basis reduction techniques are explored in [1,25]; Mahajan and Ralphs [22] solve a subproblem to find a disjunction that closes the duality gap by a certain amount. The largest set of directions is the set Z n , in which case the algorithm uses general disjunctions.…”
Section: Introductionmentioning
confidence: 99%